Negative scope ambiguity in serial verb constructions in Jordanian Arabic: an experimental investigation - Eman Al Khalaf; Nisreen Al-Khawaldeh; Bassil Mashaqba (Cogent Arts & Humanities)
This article provides a systematic investigation of serial verb constructions in Jordanian Arabic, reporting the results of two experiments. Experiment 1 (n = 86) involves an acceptability judgment task where participants rated serialized and non-serialized verbs on a 5-point Likert scale. The results of this experiment indicate that speakers of Jordanian Arabic find the serialized verbs to be as attested as their non-serialized counterparts. Experiment 2 (n = 61), a picture truth-value judgment task, tested sentences with negation in the context of SVCs to test previous claims about semantic scope ambiguity in SVCs. The results show that SVCs in Jordanian Arabic exhibit negative scope ambiguity. The article then sketches an analysis of the results of the empirical investigation in terms of generative syntax, building on an introspective investigation. This study offers new empirical material from Jordanian Arabic, an under-documented language in this respect. It also provides important insights into the syntax of verb serialization and how this structure interacts with negation in natural languages.